Cooperation of Oncolytic Herpes Virotherapy and PD-1 Blockade in Murine Rhabdomyosarcoma Models - Chun-Yu Chen (Nature Portfolio, 2017)
Abstract Oncolytic virotherapy is an effective immunotherapeutic approach for cancer treatment via a multistep process including direct tumor cell lysis, induction of cytotoxic or apoptosis-sensitizing cytokines and promotion of antitumor T cell responses. Solid tumors limit the effectiveness of immunotherapeutics in diverse ways such as secretion of immunosuppressive cytokines and expression of immune inhibitory ligands to inhibit antitumor T cell function. Blocking programmed cell death protein (PD)-1 signaling, which mediates T cell suppression via engagement of its inhibitory ligands, PD-L1 or PD-L2, is of particular interest due to recent successes in many types of cancer. In syngeneic murine rhabdomyosarcoma models, we found that M3-9-M (MHC I high) but not 76-9 (MHC I low) tumors respond to oncolytic herpes simplex virus-1 (oHSV-1) and PD-1 blockade combination therapy. In addition, the therapeutic outcomes in M3-9-M tumor models correlated with the increased incidence of CD4+ and CD8+ T cells but not with the CD4+CD25+Foxp3+ regulatory T cell populations in the tumor. Overall, our data suggest the combination of PD-1 blockade and oHSV-1 may be an effective treatment strategy for childhood soft tissue sarcoma.